Mineralogical Characteristics of Skarn in Tuosibasitao Iron-Copper-Gold Deposits of the Northern Margin of Junggar, Xinjiang, and Their Geological Significance - LV Shu-jun; YANG Fu-quan; CHAI Feng-mei; ZHANG Zhi-xin; LI Qiang (Yankuang ceshi, 2013)
The Tuosibasitao Fe-Cu-Au mineral deposit mainly occurs in the contact zone between the diorite porphyrite and basaltic volcanic rock of Middle Devonian Beitashan Formation in the forms of massives, heterogeneous gobbets, veinlets, breccia and veinlet-disseminated. The ore bodies in the ore deposit occur as stratoids or lenses, surrounded by skarn. The major and trace elements in magnetite, and chemical components in garnet, chinopyoxene and epidote from Tuosibasitao deposit were studied by Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) and Electron microprobe analyse. The results demonstrate that the end member of garnet is mainly grossularite and andradite. The composition of pyroxene was mainly diopside, with a small amount of augite. The epidote was enriched in Fe and Ca. The composition of these skarn minerals suggest that skarn in Tuosibasitao ore deposit is calcic skarn. In combination with the geological characteristics, it is possible that the skarns are formed by hydrothermal interaction with metamorphic volcanic, and the formation of magnetite is related to the retrogressive metamorphism of the skarn. Copper and gold mineralization occurred during the quartz-sulphide- carbonate period.